Piano Variations, Rondos and Mischellaneous Pieces for Keyboard [de Wolfgang Amadeus Mozart] = Variationszyklen und Einzelstücke für Klavier [von Wolfgang Amadeus Mozart] = Variations pour piano et pièces diverses pour clavecin ou piano [de Wolfgang Amadeus Mozart] = Variazioni per pianoforte e altre composizioni per clavicembalo o pianoforte [di Wolfgang Amadeus Mozart] - Mozart, Wolfgang Amadeus ((Complete Mozart Edition ;)
Contiene: KV 24, KV 25, KV 179, KV 180, KV 264, KV 265, KV 352, KV 353, KV 354, KV 398, KV 455, KV 500, KV 573, KV 613, KV 355, KV 397, KV 485, KV 511, KV 540, KV 574, KV 33B, KV 395, KV 408 Nº 1, KV 394 5a, KV 312, KV 399, KV 400, KV 460, KV 453a, KV 4, KV 94, KV 1a, KV 1b, KV 1c, KV 1d, KV 2, KV 3, KV 5, KV 1+1f, KV 401.